2021
DOI: 10.1111/bpa.12942
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive decline in amyotrophic lateral sclerosis: Neuropathological substrate and genetic determinants

Abstract: Cognitive impairment and behavioral changes in amyotrophic lateral sclerosis (ALS) are now recognized as part of the disease. Whether it is solely related to the extent of TDP-43 pathology is currently unclear. We aim to evaluate the influence of age, genetics, neuropathological features, and concomitant pathologies on cognitive impairment in ALS patients. We analyzed a postmortem series of 104 ALS patients and retrospectively reviewed clinical and neuropathological data. We assessed the burden and extent of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Frontotemporal lobar degeneration explains cognitive impairment only in some ALS patients, while other features such as the extent of TDP-43 pathology and the presence of hippocampal sclerosis may also contribute to cognitive disturbances [ 33 ]. Neuroimaging studies have shown the involvement of extra-motor brain regions such as the hypothalamus [ 34 ], frontotemporal areas, cerebellum, and basal ganglia [ 35 , 36 , 37 , 38 ].…”
Section: Non-motor and Non-sensory Alterations In Alsmentioning
confidence: 99%
“…Frontotemporal lobar degeneration explains cognitive impairment only in some ALS patients, while other features such as the extent of TDP-43 pathology and the presence of hippocampal sclerosis may also contribute to cognitive disturbances [ 33 ]. Neuroimaging studies have shown the involvement of extra-motor brain regions such as the hypothalamus [ 34 ], frontotemporal areas, cerebellum, and basal ganglia [ 35 , 36 , 37 , 38 ].…”
Section: Non-motor and Non-sensory Alterations In Alsmentioning
confidence: 99%
“…When studied with specifically designed instruments, such as the Edinburgh ALS cognitive and behavioral screen (ECAS), the ALS cognitive behavioral screen, or the Arrows and Colors Cognitive Test, up to 20% of patients with ALS can also be diagnosed with FTD, and up to 50% of patients with ALS have a cognitive or behavioral impairment (ALScbi) ( 6 , 10 , 32 36 ). The frequency and characteristics of cognitive and behavioral impairment resemble those noted in FTD, and recent neuropathological studies have reported frontotemporal involvement consistent with the diagnosis of FTLD in more than 30% of patients with ALS ( 37 ). Among the most common cognitive symptoms developed in patients with ALS-FTD are executive dysfunction, language impairment, and social cognition, all of which are linked to the frontal and temporal lobes ( 6 , 33 ).…”
Section: Extra-motor Involvement In Alsmentioning
confidence: 77%
“…Notably, the degree of synapse loss correlated with the severity of the patients' cognitive impairment independent of cortical atrophy, supporting the idea that synapse loss precedes neuronal loss ( 109 , 110 ). Finally, Tau pathology and hippocampal sclerosis may also play a secondary role in the presence of cognitive impairment in patients with ALS ( 37 , 111 , 112 ).…”
Section: Extra-motor Involvement In Alsmentioning
confidence: 99%
“…57 Cognitive dysfunction and extramotor atrophy in ALS was found to be influenced by a polygenic risk profile due to a range of genetic polymorphisms, 34 while cognitive decline in ALS patients was more likely to occur in those with more extensive TDP-43 deposition and additional neuropathological features typical of FTLD. 35 The emergence of cognitive phenotypes across the spectrum of amyotrophic lateral sclerosis-frontotemporal dementia (ALS-FTD) and more widespread TDP-43 deposition appears to depend on the expression of particular protein networks, in particular networks enriched with ribonucleic acid (RNA) binding proteins, and markers of microglial function also appear to drive phenotypic expression. 33 Several studies establish the association between expansions in C9orf72, ALS and frontotemporal dementia (FTD), strengthening the notion that these clinical phenotypes exist on a continuum, while also identifying the neuropathological hallmarks of this mutation, notably the presence of p62 positive inclusions and dipeptide repeat aggregates.…”
Section: Clinico-pathological Studiesmentioning
confidence: 99%